Pendidikan Kesehatan Sebagai Upaya Pencegahan Terjadinya Intrauterine Fetal Death (IUFD) Pada Ibu Hamil - Hasna, Gina; Hasanah, Hilmiatun; Khotimah, Husnul; Mustakimah, Risma (Yayasan Inspirasi El Burhani, 2024)
Introduction: Intrauterine Fetal mortality (IUFD) is defined as fetal mortality after 20 weeks of gestation and is divided into two types: early IUFD and late IUFD. If the fetal death happens before 24 weeks of gestation, it is considered early IUFD; if the fetal death occurs beyond 24 weeks of gestation, it is considered late IUFD. Objective: Aims to expand awareness and increase knowledge of pregnant women regarding the incidence of Intrauterine Fetal Death (IUFD) in order to prevent and reduce the prevalence of Intrauterine Fetal Death (IUFD) in pregnant women Method: The method used is a qualitative approach by providing education in the form of health education to pregnant women at the Banjarsari Community Health Center, Ciamis Regency on 17 November 2023 who have met the inclusion and exclusion criteria with a total of 6 participants. The parameters used in measuring knowledge use the interview method and giving questionnaires. Result: The results showed that all participants did not know about Intrauterine Fetal Death (IUFD) in pregnant women. Meanwhile, after implementing health education regarding Intrauterine Fetal Death (IUFD), all participants knew about the health problem of Intrauterine Fetal Death (IUFD) Conclusion: The end of the implementation of the health education initiative on Intrauterine Fetal Death went smoothly, as expected. This health education is useful and beneficial for pregnant women in the Banjarsari Community Health Center area. This is proven by the participants' interest and active participation in this health education, as well as increasing knowledge about Intrauterine Fetal Death in pregnant women before and after the education.